Finding refuge in Europe: The influence of the EU's internal normative power as a human rights actor on its migration crisis responses - Manalo, Shayne Clarys D. (Animo Repository, 2022)
In the course of the 2015 migration crisis, the human rights of migrants and refugees have been neglected and undermined by responsible authorities. The right to seek asylum has never been more significant than it is now due to the amount of violence, wars, persecution, and armed conflicts occurring across the world. Questions surrounding the ability of the EU to act as a normative power have been debated in the international relations narrative for quite a while. This study hypothesized that there is an inconsistency between the EU’s human rights rhetoric and the EU Member States’ human rights practice in response to the migration crisis, which led to the ineffectiveness of the EU’s internal normative influence. The study utilized Ian Manners’ (2002) Normative Power Europe theory through a congruent triangulation mixed method analysis to test the hypothesis. For the data collection, the researchers performed a qualitative analysis of human rights rhetoric using the EU’s official documents and videos and a quantitative analysis of human rights practice using a derived questionnaire from the Freedom in the World Research Methodology. In this light, the study pursued this research design through a top-bottom approach to determine the effectiveness of the EU as an internal normative power and a human rights actor during its response to the migration crisis from 2016 to 2018 in hotspot countries, Greece and Italy. The study sought to assess the level of consistency between the human rights rhetoric and practice and its impact on the internal normative influence on the migration responses of hotspot countries. The study's qualitative evaluation found that the EU institutions are in consensus on funding humanitarian organizations' integration programs. Similarly, the institutions were active in persuading Member States to participate in the Relocation Scheme and aid Greece and Italy with their humanitarian needs. The findings indicated that Greece and Italy's freedom statuses are both partly free, as evaluated by the derived FIW questionnaire. Following the triangulation analysis, it was also determined that the EU's human rights rhetoric is partly consistent with the human rights practice of the EU hotspot countries. Based on these results, it has been concluded that the EU demonstrated limited effectiveness in its internal normative power influence, thereby affecting its credibility as a human rights actor to Greece and Italy. Recommendations for further research on normative power, human rights, and migration were derived at the end of the study. With a vision of a society in which refugee rights are actively promoted and protected, this thesis hoped to contribute new and significant knowledge on how the development of existing human rights instruments can result in more efficient crisis responses and how the EU operates amidst the contemporary challenges of the migration-human rights nexus. Keywords: European Union, Migration Crisis, Normative Power Europe, Internal Dimension, Human Rights, Consistency, Migrants, Refugees